A power-sharing perspective on employees’ participatory influence over organizational interventions: conceptual explorations - Lundmark, Robert (Frontiers in Psychology, 2023)
A participatory approach is widely recommended for organizational interventions aiming to improve employee well-being. Employees’ participatory influence over organizational interventions implies that managers share power over decisions concerning the design and/or implementation of those interventions. However, a power-sharing perspective is generally missing in organizational intervention literature. The aim of this paper is therefore broaden the picture of the mechanisms that influence, more or less, participatory processes by conceptually exploring this missing part to the puzzle. These conceptual explorations departs from both an empowerment and a contingency perspective and results in six propositions on what to consider in terms of power-sharing strategies, reach, amount, scope, culture and capacity. Implications for research, as well as for organizations and practitioners interested in occupational health improvements, are then discussed. Especially, the importance of aligning power-sharing forms with the needs of the participating employees, and taking factors that can facilitate or hinder the power-sharing process into consideration, are stressed. The importance of training managers in power-sharing practices and supporting a participatory process is also highlighted.